A study on Green IT awareness among University Malaysia Pahang students - Farghaly, Alaa Taiseer; Mazlina, Abdul Majid (2019)
This current study Investigate and Assessment the awareness of Green IT Practices Among University Student. Green IT acts as a fundamental vector that can contribute greatly towards productivity. Its sectors have been greatly responsible for energy consumption, waste generations and gas emissions. Green IT approach can seriously answer these problems and improve organizational sustainability by increasing environmental performance. There are many practices has been done to achieve sustainability, the most practiced of these are reduce, reuse, and recycle. The aim of this study is, to assess the green IT awareness among UMP students through survey method, and to develop a green IT website for rising the awareness of green IT concept. This study finds that the awareness of Green IT Practices Among UMP Students is low. So that this study develops a green IT website for rising the awareness of green IT concept.